1998
DOI: 10.1029/97jd02850
|View full text |Cite
|
Sign up to set email alerts
|

Application of the dispersion formula to long‐and short‐period gravity waves: Comparisons with ALOHA‐93 data and an analytical model

Abstract: Abstract. During the Airborne Lidar and Observations of Hawaiian Airglow (ALOHA)Campaign on October 10, 1993, a wave structure with a sharp front covering significant parts of the sky was observed to move with a phase velocity of 76 m/s at a period of 4 to 5 min. Simultaneous observations of the Green line and the OH emission brightness showed a 180 ø phase diffeence. We have two objectives. (1) By using a dispersion formula, we first separated the true partial wave guidance for long-period waves from the back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
4
23
1
Order By: Relevance
“…However, while this approach can lead to the observed varicosity in the 557.7 OI and OH layers (contrary to the Smith et al [2003] statement), this approach fails to describe all of the features of the observations. For example, as pointed out in the Munasinghe et al [1998] study, their model does not account for the speed of the event or the dc airglow component after the front. This study had to invoke ideas from the Dewan and Picard [1998] bore theory to improve the description of the observations.…”
Section: A Review Of Mesospheric Bores Ducted Gravity Waves Walls mentioning
confidence: 97%
See 1 more Smart Citation
“…However, while this approach can lead to the observed varicosity in the 557.7 OI and OH layers (contrary to the Smith et al [2003] statement), this approach fails to describe all of the features of the observations. For example, as pointed out in the Munasinghe et al [1998] study, their model does not account for the speed of the event or the dc airglow component after the front. This study had to invoke ideas from the Dewan and Picard [1998] bore theory to improve the description of the observations.…”
Section: A Review Of Mesospheric Bores Ducted Gravity Waves Walls mentioning
confidence: 97%
“…A second explanation of these mesospheric fronts involves gravity waves propagating within a thermal or dynamical duct (commonly referred to as a Doppler duct) existing in the mesosphere/lower thermosphere [ Isler et al , 1997; Walterscheid et al , 1999; Hecht et al , 2001]. For example, Munasinghe et al [1998] proposed an alternative explanation for the Taylor et al [1995] event, suggesting that it could be the result of a two‐node fully guided mesospheric duct. However, while this approach can lead to the observed varicosity in the 557.7 OI and OH layers (contrary to the Smith et al [2003] statement), this approach fails to describe all of the features of the observations.…”
Section: A Review Of Mesospheric Bores Ducted Gravity Waves Walls mentioning
confidence: 99%
“…Their follow‐up paper [ Dewan and Picard , 2001] suggested that mesospheric bores may occur as the result of a gravity‐wave/critical‐layer interaction with the mean wind flow and that both the resulting inversion layer and the bore share a common origin. Munasinghe et al [1998] suggested that the same wave event could be explained by the interaction of two tidal modes within a ducting region but this explanation fails to explain the sudden emission increase just prior to the wave train or the emission intensity complementarity exhibited by the wave patterns in the nightglow layers during such events. Another similar event was reported by Swenson and Espy [1995]; their so‐called “wall” event was interpreted as being the leading edge of a large internal gravity wave [ Swenson et al , 1998] whose passage rendered the local medium super‐adiabatic.…”
Section: Introductionmentioning
confidence: 99%
“…Dewan and Picard (2001) further reported that mesospheric bores might be formed as a result of interaction between the gravity wave and a critical layer under a mean wind flow. Munasinghe et al (1998) suggested that such a wave event could be explained by an interaction of two tidal modes within a ducting region. This explanation however could not explain a sudden emission increase just prior to the wave train and the out of phase intensity variation between the two emission layers (complementary effect).…”
Section: Introductionmentioning
confidence: 99%